REHABILITATION OF PATIENTS WITH THE USE OF DENTAL IMPLANTS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Dental implants have become a cornerstone in modern dentistry, offering an essential solution for patients needing oral rehabilitation. By integrating advanced biomaterials, refined surgical protocols, and patient-specific treatment planning, dental implants significantly restore masticatory function, improve aesthetics, and enhance overall quality of life. This article explores the current approaches to patient rehabilitation through dental implants, examining the effects of implant design, osseointegration, prosthetic considerations, and multidisciplinary care. Attention is given to crucial aspects such as preoperative evaluation, the integration of digital dentistry, and long-term maintenance strategies. By synthesizing evidence from randomized controlled trials, cohort studies, and systematic reviews, we highlight the efficacy, challenges, and emerging research directions in implant-based rehabilitation. Ultimately, an integrated, patient-centered strategy that leverages technological advancements, careful planning, and robust follow-up protocols remains vital for successful clinical outcomes.